16x = 4 Divide both sides by '16' Hence 16x/16 = 4/16 x = 4 / 16 x = 1/4
x2 - 16x + 28 = x2 -2x - 14x - 28 = x(x - 2) - 14(x - 2) = (x - 14)(x - 2)
To simplify the expression 16x - 8 - 5 - 6x - 4, first combine like terms. Combine the x terms by subtracting 6x from 16x to get 10x. Then, combine the constants by adding -8, -5, and -4 to get -17. Therefore, the simplified expression is 10x - 17.
In the absence of signs I have assumed the term in 16x and 60 are negative: ie x2 - 16x = -60 or x2 - 16x + 60 = 0 Factors of 60 which total -16 are -6 and -10, so (x - 6)(x - 10)
X2 - 16X + 15 = 0 (X - 1)(X - 15) = 0 So X -1 = 0 or X - 15 = 0 ie X = 1 or X = 15
16x = 55Therefore, x = 55/16x = 3.4375
To factorise x3 + 5x2 - 16x - 80 I note that -80 = 5 x -16 and 5 & -16 are the coefficients of x2 and x. Thus I have: x3 + 5x2 - 16x - 80 = (x + 5)(x2 - 16) and the second term is a difference of 2 squares, meaning I have: x3 + 5x2 - 16x - 80 = (x + 5)(x + 4)(x - 4)
NOTE: xx can be written as x^2 i.e. x squared 3x^2 + 16x + 5 = 3 x^2 + x + 15x + 5 (Since 16x = x + 15x) = x ( 3x + 1 ) + 5 ( 3x + 1 ) = ( x + 5 ) ( 3x + 1 ) Therefore the factors are ( x + 5 ) and ( 3x + 1 )
x2 - 16x + 68 = 5 (x - 8)2 + 4 = 5 (x - 8)2 = 1 x - 8 = 1 or -1 x = 9 or 7
(x - 5)(x - 11)
(3x + 1)(x + 5)
(3x + 1)(x + 5)
(x + 5)(3x + 1)
2 * 2 * 2 * 2 * x * x * x = 16x^3
√(16x) = 4√x = 4x1/2
8-8x=8x+18 Through simple algebra, this can be manipulated to solve for x: 8=16x+18 -10=16x -5/8=x
16x = 4 Divide both sides by '16' Hence 16x/16 = 4/16 x = 4 / 16 x = 1/4